The Synthesis and Crystal Phase Evolution of SiO2-Stabilized Zirconia Nanocomposites at Low Temperatures for the Production of Zircon - Akbarpour, Sepide; Khoshandam, Behnam; Maroufi, Samane (Journal of materials engineering and performance, 2023)
The aims of this paper were to reduce the operating temperature of SiO 2 -stabilized zirconia synthesis compared to previous works and produce a practical ZrSiO 4 ceramic by the solution combustion method. The analysis of DSC, XRD, FTIR, FE-SEM, TEM, SAED, HR-TEM and Rietveld refinement were used to characterize the resulting products. The results demonstrated that the type and amount of fuels (i.e., urea and glycine) were important factors in self-sustained reaction and crystalline structures of zirconia. A comparison was also done to study the impact of the calcination temperature on the phase evolution of stabilized monoclinic zirconia, obtained 96.67% of m-ZrO 2 with crystallite size of 31 nm. Finally, sintering process of m-ZrO 2 was applied to synthesize ZrSiO 4 . The crystallization of ZrSiO 4 from the binary system of m-ZrO 2 and SiO 2 has been the subject of extensive study, commonly obtained with cations at high temperatures. Interestingly, the present study achieved ZrSiO 4 without the presence of cation at low temperature, and indicated 79.51% purity with compressive strength and Vickers hardness of 416.38 ± 6.79 MPa and 1143.2 ± 40.2 HV (11.21 ± 0.39 GPa), respectively. Due to appropriate appearance color and excellent mechanical properties of ZrSiO 4 synthesized at low-temperature processing, this approach can be promising for the biomedical application. Graphical Abstract